Control of Electric Car Wheel Rotation Speed Using an Accelerometer Sensor (MPU-6050) - Faalah, Fadjar Nur; Hanna, Ahmad Zyusrotul; Ma'arif, Alfian (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
In the modern era, the implementation of electrification technology is one of the efforts that needs to be applied to create fuel-efficient and environmentally friendly vehicles. This technology encompasses various types, ranging from hybrid to full electric vehicles. There are four types of electric vehicle drivetrains and power sources used, namely: Battery Electric Vehicle (BEV), Hybrid Electric Vehicle (HEV), Plug-in Hybrid Electric Vehicle (PHEV), and Fuel Cell Electric Vehicle (FCEV). The prototype system of an electric car aims to create an Electrical Control Unit (ECU) with a feature that enhances acceleration in a multifunctional electric car, which can be used in both conventional and unconventional vehicles, such as Formula-E racing cars. The participation in creating an electric car prototype is used for testing the speed control of electric cars using an accelerometer sensor (MPU-6050) placed on the steering wheel, similar to electrification technology. The drivetrain technology aims to improve acceleration (the change in speed within a specific time unit) in electric cars. The components used in creating the electric car prototype include the main components such as the Arduino Uno R3 microcontroller, MPU-6050 sensor, and potentiometer.